Ultra Low-Coverage Whole-Genome Sequencing as an Alternative to Genotyping Arrays in Genome-Wide Association Studies - Chat, Vylyny; Ferguson, Robert; Morales, Leah; Kirchhoff, Tomas (Frontiers in Genetics, 2022)
An array-based genotyping approach has been the standard practice for genome-wide association studies (GWASs); however, as sequencing costs plummet over the past years, ultra low-coverage whole genome sequencing (ulcWGS <0.5X coverage) has emerged as a promising alternative that provides superior genomic coverage with substantial reduction of genotyping cost. To evaluate the potential utility of ulcWGS, we performed a whole genome sequencing (WGS) of 72 European individuals to a target coverage of 0.4X, and compared its performance with the widely used infinium global screening multi-disease array (GSA-MD). We showed that the number of variants captured by ulcWGS is comparable to imputed GSA-MD platform, particularly for low-frequency (95.5%) and common variants (99.9%), with high imputation R2 accuracy (mean 0.93 for SNPs and 0.86 for indels). Using deep-coverage 30X WGS as the “truth” genotypes, we found that ulcWGS has higher overall non-reference genotype concordance compared to imputed GSA-MD for both SNPs (0.90 vs. 0.88) and indels (0.86 vs. 0.83). In addition, ulcWGS proved to be as sensitive as genotyping-based method in ancestry prediction producing similar principal component (PC) scores. Our findings provide important evidence that the cost efficient ulcWGS of < 0.5X generates high genotype accuracy, outperforming the standard genotyping arrays, making it an attractive alternative to the array-based method in next generation GWAS design.